Designed to sell : the evolution of modern merchandising and display - Wood, Alessandra (Abingdon, Oxon New York, NY : Routledge, 2020)
"Designed to Sell presents an engaging account of mid-twentieth century department store design and display in America from the 1930s to the 1960s. It traces the development of post-war philosophies of retail design that embodied aesthetics and function and new modes of merchandise display, resulting in the emergence of a new type of industrial designer. The evolution of aesthetics in department stores during this period reflected larger cultural shifts in consumer behaviour and lifestyle. Designed to Sell explores these changes using five key case studies and original archival sources to reveal the link between designers and consumption beyond the design of individual objects. It argues that design is not simply connected to retail consumption, but that it is capable of controlling how and where customers shop and what they are drawn to purchase. This book contextualises this discussion and brings it up to date for students and scholars interested in design, retail and interior history"--
OCLC-licensed vendor bibliographic record.
Keywords: Department stores -- United States -- History -- 20th century; Retail trade -- United States -- History -- 20th century; Marketing -- United States -- History -- 20th century; Consumer behavior -- United States -- History -- 20th century; ARCHITECTURE / General; ARCHITECTURE / Interior Design / General; ARCHITECTURE / Interior Design / Lighting